Using Reflecting Teams in Clinical Training - Paré, David A. (Canadian Journal of Counselling and Psychotherapy, 2007)
The reflecting team offers a useful process for both giving counsellors in training the opportunity to try out the ideas and practices they are learning, as well as providing potentially therapeutic input to clients. This paper recounts a brief history of the reflecting team's development, followed by an examination of the social constructionist underpinnings of reflecting team work. The author suggests a range of guidelines for using reflecting teams in clinical training, followed by a clinical illustration of the process in action.